PERSAINGAN IDEOLOGI DAN MUATAN PROPAGANDA DALAM DRAMA SEMASA PENDUDUKAN JEPUN DI INDONESIA: IDEOLOGICAL CONTESTATION AND PROPAGANDA CONTENT IN DRAMAS DURING THE JAPANESE OCCUPATION IN INDONESIA - Dewojati, Cahyaningrum (Jurnal Pengajian Melayu (JOMAS), 2020)
This research aimed to analyze ideological contestation and propaganda content in drama texts written during the Japanese Occupation in Indonesia. The drama texts used are ‘Kami, Perempoean’ by Asia Poetera (in Dewan Kesenian Jakarta, 2018) and ‘Pandu Partiwi’ by Merayu Sukma (in McGlynn, et al (eds.), 2006). The approach of this research utilised Gramsci’s theories on hegemony and ideology. Within both texts, there was an ideological contestation between Asian nationalism and Western colonialism. An ideological contestation between humanism and nationalism was also identified in both texts. In addition, Japanese propaganda was detected in ‘Kami, Perempoean’ and ‘Pandu Partiwi’ as a call for collaboration with various organisations established by the Japanese. There were also anti-West sentiments and an emphasis towards specific interests of Japan. Keywords: ideology, contestation, Japanese, drama texts, propaganda.